UPAYA MENINGKATKAN KREATIVITAS MENGGAMBAR MELALUI MEDIA GAMBAR PADA ANAK KELOMPOK B PAUD IKHSANUL KAMIL - Sari, Mutia; Agustin, Melisa Della (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
This research background by the problem to the children ability in improving creativity has not developed optimally, children still can not draw well, children look unhappy and horn to do drawing activity. This study purpose to improve the creativity of drawing for children of B1 PAUD Ikhsanul Kamil through the picture media. This research is a qualitative research with classroom action research (PTK) conducted in 2 cycles. The subjects of this study were the children of group B1 PAUD Ikhsanul Kamil, which amounted to 15 children. Data collection techniques used in this study were observation, interview and documentation. The data collection instrument uses a child's observation sheet. The ability to improve the creativity of drawing is said to succeed when the percentage of creativity reaches 81% with the criteria growing very well. The ability of creativity to draw prestige of children percentage of 34.71%. Ability of creativity of drawing for child of group B1 through picture media at cycle I percentage equal to 62,47%. Research on the first cycle has succeeded in improving the ability of drawing creativity but has not achieved the success indicator so that it is continued in the next cycle. The result of the average percentage of cycle II shows the achievement of the child's ability that Develops Very Good (BSB) with average value amounted to 86.38%. Based on the results of research that efforts to improve the ability of drawing creativity for children group B1 Paud Ikhsanul Kamil through picture media can be improved.